Backpacking’s Run-In with McDonaldization Theory - Rizky Amalia (Rubikon : Journal of Transnational American Studies, 2017)
Vacation, unconsciously, has been one of the basic needs in human’s life. It provides a break from the usual routine activity which somehow can trap the doer into an autopilot mode; leaving them to encounter a seemingly never ending task. Thus, vacation’s purpose is to experience a different setup that is not usually found in everyday lives. This study focuses on how vacation has been set up in such a way that violates its initial purpose. Using the theory of McDonaldization proposed by George Ritzer, the discussion will flow into breaking down four concepts of the theory to be matched with the premise of backpacking; in which suggests a possibility of deconstructing vacation concept that is familiar in modern setting. However, with the development of era, backpacking slowly transforms into following the concept of McDonaldization in tourism, giving a glimpse on how modernity has touched every aspect of human’s life and making what was once a breakthrough in tourism world a cliché that falls through some anticipated pattern. Keywords: Backpacking, McDonaldization, Vacation